HUMAN – PRIMATES CONFLICT IN BANGLADESH: A REVIEW - M. M. Uddin; M. F. Ahsan; H. Lingfeng (Journal of Animal and Plant Sciences, 2020)
Human-primates conflict is an important issue for the conservation of primate biodiversity globally. We reviewed research papers that have been published over the last 20 years on Bangladesh regarding the human-primates conflicts. We also identified primate species are involved in conflict, crop damage preference by primates and local peoples' perceptions towards primates. Our study suggests that three species (Rhesus macaque Macaca mulatta, Capped langur Trachypithecus pileatus, and Common langur Semnopithecus entellus) are mostly involved in the conflict with humans. Crop damage is the main cause of human-primates conflict in Bangladesh. Decreasing of forest covers and increasing of human settlements in and around the forests are responsible for enhancing conflict with the non-human primates. Moreover, people’s aggressive behaviors are responsible to cause primates to conflict with humans. People perception mostly towards the non - forested primate species are more aggressive than forested primate, this is due to economic damages to the local people by primates. The progress of research regarding human-primates conflict indicates that after 2011, researchers are more concerned with human-primates conflict research than in or before 2001. This concerned attention of researchers about human-primates conflicts indicates that in Bangladesh these types of conflict may increase in the future.
Keywords: Human-primates conflict; crop damage; Bangladesh